Sumatriptan Succinate Hemi(Ethanol Solvate) - Petr A. Buikin; Anna V. Vologzhanina; Alexander A. Korlyukov (Molbank, 2024)
1-(3-(2-(Dimethylammonio)ethyl)-1H-indol-5-yl)-N-methylmethanesulfonamide succinate (sumatriptan succinate, HSum+·HSucc−) is a serotonin receptor agonist used to treat migraines. By the recrystallization of this substance from ethanol, its hemi(ethanol solvate), HSum+·HSucc−·0.5EtOH, was obtained. The solid was characterized by X-ray diffraction and FT-IR spectroscopy. In HSum+·HSucc−·0.5EtOH, solvent molecules link succinate anions into infinite O–H…O bonded chains, which are further connected by N–H…O interactions with cations into H-bonded layers.